Integrasi Agama Dan Budaya Model Tasawuf - Nuralim, Iik; Azis, Dony Khoirul (Tasamuh: Jurnal Studi Islam, 2023)
In the Islamic world, the development of Sufism seems to have started from the individual activities of Sufi experts. They have almost no ability to transfer their knowledge to others. This is because Sufism is actually not properly called science in the sense that it consists of empirical, logical, rational and systematic facts. Sufism can best be described as a collection of experiences of communing with the Divine Light which is full of taste and manifests itself in various forms of life which shun luxury, spend time in worship, desire to meet God and be available in all things. time. called to God. The integration of religion, tasawwuf and culture into their relationship will show the same thing. Likewise in culture, because culture is reality, which is created, produced, shaped and institutionalized. So actually religion is always synonymous with tradition, because culture is an expression of people's belief in something sacred. If the relationship between religion and tradition is put forward as a form of cultural interpretation, then all realms of religion are related to human creativity. That is, the religious truth that everyone believes to be "true" is basically limited to what people can interpret and express about "truth", God is absolute